(untitled) (SCIENCE TIME JOURNAL, 2025)
This article examines the criteria and strategies for selecting and using video materials in English language teaching (ELT). It synthesizes theoretical perspectives, such as Mayer’s Cognitive Theory of Multimedia Learning, and practical frameworks proposed by Gallacher, Stempleski, Sherman, and Wedlock & Binnie. The analysis highlights content appropriateness, learner proficiency level, clarity of message, authenticity, and motivational value as central criteria for effective video integration. The study concludes that while Mayer’s principles serve as a solid theoretical foundation, practical approaches by Gallacher and others offer more accessible guidelines for teachers. The findings suggest combining these frameworks to create a balanced methodology that supports student engagement, language acquisition, and cultural understanding.